Transcriptome responses of RNAi-mediated ETH knockdown in Scylla paramamosain at different premolt substages - Chan, Siuming-Francis; Wen, Qi-Qiao; Ao, Chun-Mei; Wang, Wei; Wang, Cheng-Gui; Zhao, Yan-Fei (Frontiers in Endocrinology, 2022)
Ecdysis triggering hormone (ETH) plays an important role in molting, reproduction, and courtship behavior in insects. To investigate the potential downstream pathways and genes of ETH in Scylla paramamosain, RNA interference (RNAi) was conducted on crabs at early (D0) and late (D2) premolt substages, and the transcriptome profiles of each group were compared by RNA sequencing. Real-time quantitative polymerase chain reaction (RT-qPCR) and semiquantitative polymerase chain reaction (RT-PCR) results showed a significant knockdown of ETH at D0 stage, whereas a significant increase was shown conversely in crabs at D2 substage after the injection of dsETH. A total of 242,979 transcripts were assembled, and 44,012 unigenes were identified. Transcriptomic comparison between crabs at D2 and D0 substages showed 2,683 differentially expressed genes (DEGs); these genes were enriched in ribosome and pathways related to transcription factor complex and cell part. Twenty DEGs were identified between dsETH-injected and dsGFP-injected crabs at D0 substage; these DEGs were involved in carbohydrate metabolism, one carbon pool by folate, and chitin binding. Twenty-six DEGs were identified between dsETH-injected and dsGFP-injected crabs at D2 substage; these DEGs were involved in calcium channel inhibitor activity, fat digestion and absorption, and cardiac muscle contraction. RT-qPCR verified the differential expression of the selected genes. In conclusion, crabs at D0 substage are more active in preparing the macromolecular complex that is needed for molting. Moreover, ETH has potential roles in carbohydrate metabolism, one carbon pool by folate, and chitin binding for crabs at D0 substage, while the role of ETH turns to be involved in calcium channel inhibitor activity, fat digestion and absorption, and cardiac muscle contraction at D2 substage to facilitate the occurrence of molting. The selected DEGs provide valuable insight into the role of ETH in the regulation of crustacean molting.